AB0203 S100A4 Serum Levels Correlate with Disease Activity, Skin Fibrosis and Lung Involvement in Systemic Sclerosis. (10th June 2014) - Tomcik, M.; Andres Cerezo, L.; Skacelova, S.; Komarc, M.; Becvar, R.; Grigorian, M.; Distler, J.H.; Senolt, L.
Abstract : Background: In our previous study we demonstrated that S100A4 is overexpressed in scleroderma (SSc) skin, SSc fibroblasts and preclinical models of SSc in a TGF-β dependent manner. We showed that S100A4 is a new regulator of TGF-β signalling and its inhibition prevents the pro-fibrotic effects of TGF-β. Inactivation of S100A4 prevented dermal fibrosis induced by bleomycin and in Tsk-1 mice. Objectives: To evaluate S100A4 in sera of SSc patients and characterize its potential association with SSc-related features. Methods: A total of 33 patients (29 females; mean age 52.8; disease duration 4.2 years; dcSSc/lcSSc =8/25) who met the ACR classification criteria for SSc and 20 healthy individuals matched by age and sex were included in this study. Serum levels of S100A4 were measured using ELISA (CycLex Co., Ltd., Nagano, Japan). CRP, ANA and ENA complex were evaluated using standard methods. SSc-related manifestations were obtained from the Czech Registry Database of patients with SSc. Skin changes were assessed using the modified Rodnan skin score (mRSS) and EUSTAR SSc activity score was determined. Data are presented as mean ± SEM. Results: S100A4 serum levels were significantly increased in SSc patients compared with healthy controls (119.2±23.4 vs. 43.9±3.3ng/ml, p=0.011). Patients with diffuse cutaneous (dc)SSc had significantly higher levels of serum S100A4 compared with patients with limited cutaneous (lc)SSc or healthy controls (201.8±53.1 vs. 92.7±24.0ng/ml, p=0.017 and 201.8±53.1 vs. 43.9±3.3ng/ml, p=0.001, respectively). Serum levels of S100A4 positively correlated with mRSS (r=0.556, p=0.001). Furthermore, S100A4 levels negatively correlated with forced vital capacity (FVC) and saturation of peripheral oxygen (SpO2) (r=- 0.362, p=0.038 and r=-0.414, p=0.029, respectively). Of particular interest, S100A4 levels positively correlated with EUSTAR SSc activity score (r=0.750, p=0.0001). However, only correlations between S100A4 and mRSS, and S100A4 and EUSTAR SSc activity score were approved at corrected level of statistical significance after Bonferroni's correction (p<0.01). The presence of autoantibodies (ANA, anti-centromere, anti-topoisomerase I), pathological capillaroscopic pattern (early, active or late), and presence of the main individual clinical symptoms of SSc did not significantly affect serum levels of S100A4. Conclusions: We demonstrate that serum levels of S100A4 are significantly increased in SSc patients compared with healthy controls. Increased levels of S100A4 are associated with dcSSc subset, skin involvement, deteriorated parameters of lung involvement and higher disease activity. These data support our previous findings on the role of S100A4 as a regulator of TGF-β induced fibroblast activation and dermal fibrosis in SSc and experimental models of SSc. Acknowledgements: Supported by IGA NT 13698-4 and MH CR 23728. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3390